Historical and Archaeological Perspectives on the Itzas of Petén, Guatemala - Rice, Don S.; Rice, Prudence M. (University Press of Colorado, 2017)
"A detailed and thorough account of the Itzas--a Maya group that dominated much of the west lowland area of Peten, Guatemala. A theoretical perspective on the origins and an overview of the social, political, linguistic, and environmental history revealed in recent surveys and excavations"--Provided by publisher.
Keywords: Excavations (Archaeology) : Guatemala : Peten (Department); Archaeology and history : Guatemala : Peten (Department); Itza Indians : Guatemala : Peten (Department) : Antiquities; Peten (Guatemala : Department) : Antiquities